The impact of basic psychological needs on academic procrastination: the sequential mediating role of anxiety and self-control - Zhaixiang Ye; Shengjie Chi; Xiaoyun Ma; Linling Pan (Frontiers in Psychology)
This cross-sectional study investigates the relationship between basic psychological needs, state anxiety, self-control, and psychological resilience in predicting academic procrastination among college students. Drawing from Self-Determination Theory, the study explores how unmet psychological needs contribute to academic procrastination through the sequential mediation of anxiety and self-control, while also examining the moderating role of psychological resilience. A sample of 612 college students participated in the study. The results reveal that basic psychological needs negatively predict academic procrastination (β = −0.14, p < 0.01) both directly and indirectly. Specifically, self-control mediates the relationship between basic psychological needs and procrastination, while anxiety and self-control serve as sequential mediators (95% CI: [−0.12, −0.06]). Furthermore, psychological resilience significantly moderates the relationship between self-control and academic procrastination (β = 0.08, p < 0.01), as well as the sequential mediation pathway. These findings underscore the critical role of psychological resilience and self-regulation in mitigating procrastination behaviors among college students, offering practical implications for educational institutions.